How we approach conservative treatment of retinoblastoma in South America in the era of local ocular treatments: A consensus of the Grupo America Latina de Oncologia Pediatrica (GALOP) - Garin, JPL (2023)
Local therapies are increasingly used for ocular preservation in retinoblastoma. In middle-income countries, these techniques pose specific challenges mostly related to more advanced disease at diagnosis. The Grupo de America Latina de Oncología Pediátrica (GALOP) developed a consensus document for the management of conservative therapy for retinoblastoma. Intra-arterial chemotherapy (OAC) is the preferred therapy, except for those with less advanced disease or age younger than 6 months. OAC allowed for a reduction in the use of external beam radiotherapy in our setting. Intravitreal chemotherapy is the preferred treatment for vitreous seeding. Enucleation is the treatment of choice for eyes with advanced disease. © 2023 Wiley Periodicals LLC.